Harnessing energy from Australian dairy waste: utilizing five methodologies. (16th July 2020) - Arefin, Md A.; Nabi, Md N.; McIntosh, Shane
Abstract: As dairy industries increase across Australia, the amount of dairy waste is also on the rise. Australia annually production stands at around 377 727 t of cheese, 273 425 t of milk powder and 92 698 t of butter, and it is the third largest exporter of milk. The waste produced by these industries is considered a potentially valuable resource, and an environmental pollutant if not appropriately managed. The focus of this review is to evaluate the potential of converting typical Australian dairy industry waste into sustainable energy. Five fundamental methods including transesterification, pyrolysis, anaerobic digestion, steam reforming, and hydrothermal carbonization are discussed. Their technological merits, demerits and adaptability from the perspective of Australia are examined. The properties of representative wastes are also considered for the different energy conversion processes. This review aims to highlight the potential use of dairy industry wastes as feedstock for the emerging renewable energy sector. © 2020 Society of Chemical Industry and John Wiley & Sons, Ltd